Perception of Melaka Tengah health staff regarding pay movement in the new remuneration system in Melaka, March 1996 - Siti ZubaidahAbd Rahman; Raja Jamaluddin Raja Abd. Majid (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
The New Remuneration system (NRS) has been implemented since 1992 to enable the public service to expand parallel to the reform in personel function in a dynamic management climate. The philosophy of the NRS is to produce government employees whom can be assessed and rewarded on merit. A cross sectional survey was carried out in March 1996 among Melaka Tengah Health personnel to study staff perception of merit pay in the New Remuneration System and to assess its association to job motivation and satisfaction. A total of261 respondent or 87.0% health personnel took part in the survey by returning a self administered questionnaire. Only 37.2% of respondents had positive perception regarding their pay movement compared to 62.8% who had negative perception. Ninety-eight percent of respondents had high level of motivation and 93.1 % had high level of job satisfaction. The factors in the NRS that is the new assessment system (SBPP), matrix pay system, quota system, performance pay and the role of the panel for the coordination of assessment and pay movement (PPG) were shown to have a significant association (p<0.05) with respondent perception on the pay movements whereby respondents with a more positive perception of these factors were shown to have a more positive perception about their pay movement. There was also a significant association (p<0.05) between job motivation and job satisfaction to staff perception about their pay movements. This study showed that respondents with positive perception about their pay movement will also have high job motivation and satisfaction. Job motivation was also shown to be linked to job satisfaction significantly whereby respondents with higher level of motivation were noted to have a higher level of job satisfaction and vice versa. There was a significant (p<0.05) difference in perception of pay movement with monthly income of respondent. Respondents with monthly income of RM 1000 and above was shown to have a more negative perception compared to those earning below RM 1000. There was significant (p<0.05) difference in motivation level with sex, monthly income, service category and educational level of respondent. It was shown that women, those with monthly income of RM 1000 and above, were from management and support group cone' and those with education level of SPM and above had a higher level of motivation. There was also significant (p<0.05) difference in job satisfiction level with sex of respondent whereby women was shown to have a higher level of job satisfaction compared to men. Problems with acceptance of the quota and matrix system was shown to be present. The implementation of the new assessment format was also identified as problematic. This study hopes to help managers identify and improve weaknesses in the assessment format and provoke a review of the matrix and quota system in deciding pay movement.